PENGARUH MIND MAPPING TERHADAP KETERAMPILAN MENULIS PUISI KELAS VIII SMPN 1 LUMAR KABUPATEN BENGKAYANG - Liberta, Liberta (Universitas Tanjungpura, 2020)
AbstractThe purpose of this study is to describe the average poetry writing skills in students with the application of the Mind Mapping Learning model, the average poetry writing skills in students with the application of the Learning Learning Model.The theory used in this research is a mind mapping learning model and writing poetry. The method used is an experimental method with a form of research Quasi Experimental Design. The design used is the Two-Group pretest-Posttest Only. The population in this study is class VIII A, VIII B, and VIII C while the samples are Class VIII A and VIII B. Data collection techniques used are direct observation techniques, measurement techniques, and documentation techniques as well as data collection tools namely guidelines or observation sheets poetry skills tests and documents.The results of data analysis show that the average pre-test experimental class with a total score of 69.38 while the post-test 76.38 and the pre-test control class with a total score of 60.96 while the post-test 66.88 and there is influence with evidence scores 1.13 and 1.28.The results of this study are expected to be useful for readers, especially Indonesian Language teachers in Lumar 1 Junior High School, Bengkayang Regency, students and subsequent researchers who use mind mapping learning object models. For teachers this mind mapping learning model can be used as a reference for teaching in class, especially in learning to write poetry.Â Keywords: Mind Mapping, Writing Poetry